Avaliação hidrogeoquímica, geofísica e geológica do Aquífero Guarani na região central e ocidental no Rio Grande do Sul - Moreno, Wilmer Emilio Garcia (2020)
The State of Rio Grande do Sul has a large part of the Guarani Aquifer, having a recharge area that is in its central and western region. This work focuses on some municipalities located in that region, namely: Santa Cruz do Sul, the Region of Quarta Colônia, Candelária and Alegrete. Currently, there is no water resources plan in the State, and, for this reason, the aim is to evaluate the hydrogeochemical, geophysical and geological characteristics of the Aquifer recharge region. Gathered data acquired in the field, which include chemical analysis of water in different wells and geophysical surveys in refraction seismic and geoelectrical methods. In addition, geological information was taken from the public database of the Groundwater Information System (SIAGAS). Therefore, it was possible to carry out the mapping of the different chemical parameters, which includes the Piper diagram in the municipalities of Candelária and Alegrete. The data obtained by geophysical methods (refractive seismic and geoelectrical survey) were analyzed based on the geological data of wells of SIAGAS, modeling different formations and static levels, such as in 2D and 3D. The results of hydrogeochemical mapping show that the municipality of Candelária is the most affected. The relationship between geochemistry and the inferred geology by geophysical methods, provides the potential of the studied site as a possible reservoir of water for human, agropastoral or industrial use. The correlation of these data provided a broad view of the aquifer recharge region.